2001
DOI: 10.1007/s005950170006
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Oral Antimicrobial Prophylaxis on Surgical Site Infection and Methicillin-Resistant Staphylococcus aureus Infection After Elective Colorectal Surgery. Results of a Prospective Randomized Trial

Abstract: The impact of oral antimicrobial prophylaxis on the surgical site infection and methicillin-resistant Staphylococcus aureus (MRSA) infection after elective colorectal surgery was evaluated by a prospective randomized single-blind study. The patients were randomly allocated to receive either mechanical bowel cleansing with polyethylene glycol alone (group 1) or mechanical cleansing plus oral antimicrobial prophylaxis with kanamycin and erythromycin for 2 days prior to surgery (group 2). In both groups, cefotiam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
2
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 17 publications
2
41
2
1
Order By: Relevance
“…We previously reported that blood loss and associated medical diseases were signifi cant risk factors affecting MRSA infection following colorectal surgery. 12 The present results are in partial agreement with those of our previous reports. Although it may be of interest to determine whether According to Japanese classifi cation of colorectal carcinoma patients who developed postoperative MRSA infection were previously carriers of MRSA, we did not preoperatively examine the carrier status of any patient in this study.…”
Section: Discussionsupporting
confidence: 96%
“…We previously reported that blood loss and associated medical diseases were signifi cant risk factors affecting MRSA infection following colorectal surgery. 12 The present results are in partial agreement with those of our previous reports. Although it may be of interest to determine whether According to Japanese classifi cation of colorectal carcinoma patients who developed postoperative MRSA infection were previously carriers of MRSA, we did not preoperatively examine the carrier status of any patient in this study.…”
Section: Discussionsupporting
confidence: 96%
“…A further three studies were excluded as they were duplicate publications using cohorts already included in the meta‐analysis11, 12, 13. The remaining 22 studies were included in the review, of which 14 were RCTs14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, and eight were observational cohorts2 4, 28, 29, 30, 31, 32, 33 ( Table 1; Table   S1, supporting information). These studies included a total of 57 207 patients.…”
Section: Resultsmentioning
confidence: 99%
“…In the 14 RCTs14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, involving 3014 patients, rates of SSI in patients given preoperative oral antibiotic prophylaxis, in combination with i.v. antibiotic prophylaxis and MBP, were compared with those in patients who received only i.v.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…), environmental factors (i.e., ventilation in operating room, sterilization of surgical instruments, etc. ), and bacterial factors are thought to be the main causes of SSI (24)(25)(26)(27)(28)(29)(30). Surgery of the colon is associated with a high incidence of SSI compared with surgery addressed to other parts of the digestive tract.…”
Section: Discussion Discussionmentioning
confidence: 99%